Social Determinants of Pulmonary Tuberculosis in Argentina - Hilal, Fernando Andrés (2019)
Background: In Argentina approximately 9,000 new cases of tuberculosis (TB) per year are recorded, representing an incidence rate of 22 cases per 100,000 inhabitants. There are no reported studies in Argentina examining the factors that influence the unequal distribution of the disease. The aim of the study was to identify the relationship between the distribution of social and economic factors and TB in Argentina between 2008 and 2012.Methods: An ecologic study involving 525 departmental jurisdictions was conducted. Simple linear regression analysis was performed, followed by multiple linear regression for each group of determinants. A final model of determinants of the incidence of TB was constructed from a model of multiple linear regression. Results: The following determinants explain 43% of the variability of the incidence rate of TB among different jurisdictions: overcrowding, the proportion of households with a sewage network, the proportion of examined patients with respiratory symptoms, and the proportion of patients who discontinued treatment. Discussion: This study makes an important contribution to a better understanding of the factors influencing the occurrence of TB in Argentina, which is the result of a multidimensional and complex process. These factors make part of the social determination of this disease.Conclusion: TB incidence is associated with different determinants, from multiple levels. Inequalities in the distribution of TB in Argentina are driven by the unequal distribution of key social determinants.